PENGEMBANGAN BAHAN AJAR BERBASIS ETNOMATEMATIKA PADA PERMAINAN TRADISIONAL KELERENG MENGGUNAKAN APLIKASI CANVA FOR EDUCATION UNTUK KELAS VI SD - Maulana, Irsyad; Sastrawati, Eka; Budiono, Hendra (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2024)
The research aims to explain the suitability of teaching materials. This type of research and development (RD) uses the ADDIE model (analysis, design, development, implementation and evaluation). The data in the research consists of qualitative and quantitative data. The research was carried out at SDN 10/IV Jambi City. Research data collection instruments include observation, interviews, questionnaires and documentation. The results of the feasibility test for teaching materials from language validation obtained an average score of 4.9 (very valid category). Media validation got an average score of 4.7 (very valid), material validation with an average score of 4.7 (very valid). The results of validating the practicality of teaching materials from educators' responses had an average score of 4.9 (very practical), and students got an average score of 4.6 (very practical). The conclusion of this research is that the development of ethnomathematics-based teaching materials for the traditional game of marbles using the Canva for education application for class VI elementary schools is very feasible (very valid and very practical).